A Descriptive Study on Attitudes toward Seeking Professional Psychological Help among Emerging Adults in a K-pop Fan Community - Wiwit Puspitasari Dewi; Wulan Dri Puspita (Universitas Negeri Semarang, 2024)
Emerging adulthood is a transition period between adolescence and adulthood, where most psychological disorders occur. Emerging adults with K-pop music preferences could also join a fan community, which brings benefits and vulnerability toward mental health because of the dynamics among fans and artists. Hence, emerging adults with mental health problems are suggested to seek a professional to get the appropriate treatment. This study aims to describe the attitude towards psychological professional help. Using the Indonesian ATSPPH-SF as the main instrument, 156 participants from a K-Pop fan community participated voluntarily. The result indicated that most participants had moderate attitudes toward seeking professional psychological help. There was no significant difference in help-seeking attitude by mental health information and visiting professional help. This study implies the importance of better education about help-seeking by introducing mental health professionals to the K-pop fan community. Future studies may consider gathering extensive data from many K-pop fan communities in Indonesia